Extensive Cerebral Venous Sinus Thrombosis during COVID-19 Infection in a Patient with Autoimmune Hyperthyroidism: A Case Report - Mohamed Amine Mnaili; Ahmed Bourazza (Assam Journal of Internal Medicine)
Cerebral venous sinus thrombosis (CVST) in the setting of coronavirus disease 2019 (COVID-19) is an uncommon phenomenon with increasing incidence. CVST is an uncommon subtype of stroke caused by thrombotic occlusion of the cerebral veins. We report the case of an adult women with headache, fever, nausea, vomiting, and no known autoimmune diseases. Diagnostics revealed elevated infammatory and hypercoagulability markers, free T4, low TSHs, and positive SARS-CoV-2 PCR. Neuroimaging demonstrated a thrombosis of the superior sagittal sinus, both right and left transverse sinus extending into the right jugular vein. A diagnosis of CVST with associated COVID-19 and hyperthyroidism was established. In patients with suspected COVID-19, especially in the presence of causes of hypercoagulability and presence of atypical features, venous sinus thrombosis needs to be kept in mind in making the differential diagnosis. Follow-up examination revealed complete symptomatic resolution and regression of thrombosis.